2005
DOI: 10.1002/jcb.20444
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid transfer protein (PLTP) mRNA expression is stimulated by developing embryos in the oviduct

Abstract: In mammal, fertilization and early preimplantation embryo development occurs in the oviduct. Evidence is accumulating that the oviductal epithelia secrete various biomolecules to the lumen during the secretory phase of the estrus cycle to enhance embryo development. This secretory activity of the oviduct is under the regulation of steroid hormones. Observations also suggested that the gametes and embryos modulate the physiology and gene-expressing pattern of the oviduct. However, the underlying molecular chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…In addition, Lee et al (2005Lee et al ( , 2006 have analyzed the interaction between embryos and oviduct in mice and their results suggested that the presence of the embryo could affect the protein expression of the mouse oviductal epithelium, as shown for the phospholipid transfer protein (PLTP) and the demilune cell and parotid protein.…”
Section: R7mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Lee et al (2005Lee et al ( , 2006 have analyzed the interaction between embryos and oviduct in mice and their results suggested that the presence of the embryo could affect the protein expression of the mouse oviductal epithelium, as shown for the phospholipid transfer protein (PLTP) and the demilune cell and parotid protein.…”
Section: R7mentioning
confidence: 99%
“…In the presence of an embryo, the mouse oviductal epithelium secretes PLTP, which showed a higher expression in the embryo-containing oviduct than in the control oviduct (Lee et al 2005). As Pltp mRNA increased in the oviductal epithelia of pregnant mice, the authors suggested that it could be involved in in vivo preimplantation embryo development (Lee et al 2005).…”
Section: Phospholipid Transfer Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…The cDNA product was diluted with distilled water to 50 mL final volume. The qPCR was performed on an iCycler (Bio-Rad, Hercules, CA) as previously described (23). Primers were designed using Primer Premier v5.0 (Premier Biosoft International, Palo Alto, CA).…”
Section: Rna Isolation and Affymetrix Microarraymentioning
confidence: 99%
“…Using subtractive suppression hybridization, differential expression of a panel of genes including phospholipid transfer protein (Lee et al, 2005) and demilune cell parotid protein (Lee et al, 2006) were demonstrated between oviducts containing preimplantation embryos and those containing oocytes (Lee et al, 2002). It is not known whether preimplantation embryos would influence the production of oviductal C3.…”
Section: Introductionmentioning
confidence: 99%